Pengembangan media pembelajaran 媒 语 [Mèiyǔ] berbasis multimedia dengan desain pembelajaran cooperative learning - Ventivani, Aiga; Muyassaroh, Lukluk Ul (2021)
Along with the times, technology in various fields is developing very rapidly. One of the developed countries that applies technology in various fields is China. The benefits of this condition have an impact on the increasingly dominating Chinese economy. Therefore, Mandarin speakers are a bridge to connect various activities related to the field of knowledge and cooperation in all aspects that exist with China. Based on the results of observations on students of the Chinese Language Education Study Program, State University of Malang, it was found that in the grammar course students were often confused or had difficulties. The solution for this is currently still minimal and there is no appropriate learning media. Researchers are looking for solutions by making media with the ADDIE development model. The results of trials that have been carried out by the learning media 媒 语 [Mèiyǔ] deserve a presentation assessment of 84.09%, while the feasibility test on the material is 83.3%. This shows that the validation of learning media materials 媒语 [Mèiyǔ] is valid.